Sphere fitting into volumetric representations of basketball throws - Yayioglu, V. D.; Aritan, S. (ISBS Proceedings Archive (Michigan), 2017)
This study aims to provide an evaluation, through some simplifications, for the most forgiving throw positions in the game of basketball throughout the playing field. For each position, throws are modelled as differential equations and then solved numerically. Given a position in the playing field, velocity vectors of successful throws constitute a solid and we fit a maximal sphere into these solids to evaluate the error tolerance for each position. A contour graph for the volumes of maximal spheres was plotted for this evaluation.